INVESTIGATION OF THE ELEMENTAL COMPOSITION OF SOME WIDELY DISTRIBUTED HELIOTROPIUM SPECIES IN UZBEKISTAN (Scientific journal of the Fergana State University, 2025)
The elemental composition of the roots and aerial parts of Heliotropium lasiocarpum and Heliotropium dasycarpum, belonging to the Heliotropium family and growing in the Fergana Valley of Uzbekistan, was studied using the ICP-OES method. A total of 21 elements were identified and classified into macroelements, microelements, essential, and heavy metals for analysis. Among the detected elements, Ca, K, and Mg were found in relatively high concentrations (above 1000 mg/kg), while Na, Fe, and Zn were present in significant amounts (50–1000 mg/kg). The Mn content was moderate (10–100 mg/kg), whereas Cr, Ni, V, Li, and Cu were found in low concentrations (1–10 mg/kg). The levels of Se, As, and Co were very low (1–5 mg/kg), and Ag, Be, Cd, and Hg were not detected. The study revealed that macroelements such as Ca, K, and Na, as well as the microelement Fe, predominated in both the underground and aerial parts of the plants. The detected concentrations of heavy metal salts complied with the requirements set by the XIII edition of the State Pharmacopoeia of the Russian Federation and the WHO standards.